Whose data is it: A Study on Privacy Issues Concerning Targeted Advertising in the Cable and Satellite TV Industries - Tamilselvam, Arthi (2006)
ABSTRACT Data and Identity theft have become very prominent and common, making breaches of privacy a sensitive issue in todays fast-paced information age. The advent of the internet and innovative technologies is posing a serious challenge in protecting the consumer and his/her privacy. In the cable and satellite TV industry, new technologies are dynamically changing traditional marketing techniques. Many organisations are now moving away from the conventional mass marketing methods to targeted advertising models, which involves gathering personal information related to consumers. This information is worth a lot of advertising dollars to the organisations involved in collecting and using this information, but what the consumer gains, or loses, as the case may be, by divulging his or her personal information to marketers has not been studied enough. It still remains an under-explored territory. Traditionally, marketers have believed that any information collected on the consumer belongs to them (Cespedes & Smith, 1993; Patterson, Malley and Evans, 1997). This dissertation throws some light on this common assumption, while trying to understand who actually owns the collected data, primarily from a consumer perspective. This study is done in the U.S. context where, by law, the consumers do not own the data but only have rights to prevent use that is out of scope under the applicable law. This is particularly interesting as it is a stark contrast to the European privacy laws which empowers consumers by giving them the power over their data (Scheer, 2003).